A simple nanoplatform of thermo-sensitive liposomes and gold nanorods to treat bone metastasis through improved chemotherapy combined with photothermal therapy - Jia Gu; Lifan Jiang; Zhongping Chen; Jun Qi (International Journal of Pharmaceutics: X)
Bone metastasis remains a clinical challenge and is still considered incurable. While nanoparticles-based drug delivery and photothermal therapy (PTT) show promise in treating subcutaneous solid tumor, their therapeutic outcome in treating bone metastasis is limited, due to the inaccessibility of bone metastatic site and the complexity of bone metastasis. Herein, we reported a simple nanoplatform composed of thermo-sensitive liposomes (TSL) and gold nanorods (GNR) to treat bone metastasis through improved chemotherapy combined with GNR-assisted PTT. Lipid combination of TSL was firstly tailored to regulate its stability under physiological condition as well as its sensitivity in responding to PTT-caused mild hyperthermia. The obtained TSL with loaded drug was then combined with GNR to form the nanoplatform through unsophisticated incubation. Cell experiments revealed that upon near-infrared (NIR) irradiation, the nanoplatform effectively inhibited the viability and migration ability of tumor cells through PTT, PTT-triggered thermo-sensitive drug release, and PTT-augmented sensitivity of tumor cells to drug. In a murine model of bone metastasis, the nanoplatform enabled effective delivery of loaded drug and GNR to bone metastatic site for rapid drug release upon local NIR irradiation. Through killing tumor cells and rebalancing the turnover of osteoclasts and osteoblasts, the nanoplatform largely preserved bone structure for pain relief and survival extension. Inspired by the simplicity of nanoplatform acquirement and treatment operation, the strategy of liposomes-based thermo-sensitive drug delivery in combination with GNR-assisted PTT is considered greatly promising in treating bone metastasis.